The Effects of Multidisciplinary Collaborative Care Program on Learning Behavior and Health of Children with Learning disabilities - Thachai, Sumalee; Kankran, Waratip; Subannapong, Chongrat (Journal of health and health management, 2021)
This quasi-experimental research design is a one-group pretest-posttest research design. The main purpose of this study was to determine the effects of multidisciplinary collaborative care program on learning behavior and health of children with learning disabilities. The sample included 23 children with learning disabilities, selected by simple random sampling. The research instruments were 1) a learning behavior assessment form (reading, writing, and calculation) 2) a health assessment form (physical, mental, and emotional, social, and intellectual). The questionnaires were approved by experts for their content validity. The index of item objective Congruence (IOC) values were .86 and .85 respectively. The overall reliability of the questionnaires, using Cronbach’s alpha coefficient, were .85 and .89 respectively. Data was analyzed using percentage, mean, standard deviation, and paired t-test. The results of this study showed that children with learning disabilities showed statistically significant individual and overall improvement in cognitive behavior and health after participating in a multidisciplinary collaborative care program (p-value < .05). However, the duration of the follow-up evaluation should be extended to better reflect the effectiveness of the multidisciplinary collaborative care program.